PENGARUH MEDIA PEMBELAJARAN SCRATCH BERBASIS KEARIFAN LOKAL TERHADAP HASIL BELAJAR MATEMATIKA MATERI SUDUT SISWA KELAS V SDN 004 SAMBUTAN - Alvionita, Fresiliya; Asrafiani Arafah, Andi; Muhlis; Hidayat, Taufik; Alif Tunru, Andi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to examine the influence of local wisdom-based Scratch learning media on the learning outcomes of mathematics corner materials of grade V students at SDN 004 Sambutan. The background of this research is based on the low mathematics learning outcomes of students, where the average score of class V only reaches 56,28, and 50% of students have not reached the Kriteria Ketercapaian Tujuan Pembelajaran (KKTP). The method used in this study was a quantitative experiment with a quasi-experimental design, involving two groups: the experimental group using Scratch media and the control group using conventional methods.The results showed that the use of Scratch learning media based on local wisdom had a significant influence on improving student learning outcomes, with the average posttest score of the experimental group reaching 82,04, while the control group was only 67,78. The hypothesis test using an independent sample t-test yielded a significance value of 0,002, indicating that Ha was accepted and H0 was rejected. This indicates that Scratch media has succeeded in improving students' understanding of the concept of corners better than conventional learning methods.This research is expected to contribute to the development of learning methods that are more effective and relevant to the needs of students, as well as encourage the integration of local wisdom in the learning process in elementary schools.